2003
DOI: 10.1080/02844310310005667
|View full text |Cite
|
Sign up to set email alerts
|

Primary Repair of the Collateral Ligament of the Proximal Interphalangeal Joint Using a Suture Anchor

Abstract: Ten out of 12 complete ruptures of the collateral ligament of the proximal interphalangeal joint were repaired primarily using a suture anchor. Active finger exercise was started gently by taping the injured finger to adjacent one one week postoperatively. All patients returned to their original occupation or sports activities within seven weeks of operation. No patients complained of pain on the involved finger at rest or during movement. There was no instability of the proximal interphalangeal joint on manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(21 reference statements)
1
5
0
Order By: Relevance
“… 7 McCue reported that early surgical repair of injuries yielded good results in young athletes who were cooperative and motivated and who had the benefit of supervised rehabilitation, 6 and Isani and Kato recommended operative repair in young workers and athletes. 4 , 5 , 10 Our results also support operative repair of collateral ligament in patients with grade III collateral ligament injury.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“… 7 McCue reported that early surgical repair of injuries yielded good results in young athletes who were cooperative and motivated and who had the benefit of supervised rehabilitation, 6 and Isani and Kato recommended operative repair in young workers and athletes. 4 , 5 , 10 Our results also support operative repair of collateral ligament in patients with grade III collateral ligament injury.…”
Section: Discussionsupporting
confidence: 68%
“…In cases where there was a remnant of the collateral ligament to suture strongly, we used suture anchors, as these provide strong mechanical stability for early motion exercises, consistent with the findings of mechanical and clinical studies. 4 , 5 , 11 , 12 , 13 We started active motion exercises of the PIP joint 3 days after the operation. Early exercise of the PIP joint is related to rapid functional recovery of PIP joint motion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is still a topic of controversy, however, with some investigators advocating repair only if there is subluxation and closed reduction is not possible, whereas others report that surgical repair is necessary, 21 especially in young workers and athletes. [22][23][24] Collateral ligaments typically fail proximally. If there is enough substance of the collateral ligament on the condyle of the proximal phalanx, it may be repaired directly.…”
Section: Treatment Of Proximal Interphalangeal Joint Collateral Ligammentioning
confidence: 99%